IS3 profiling identifies the enterohaemorrhagic Escherichia coli O-island 62 in a distinct enteroaggregative E. coli lineage - Okeke Iruka N; Macfarlane-Smith Louissa R; Fletcher Jonathan N; Snelling Anna M (Gut Pathogens, 2011)
Abstract Background Enteroaggregative Escherichia coli (EAEC) are important diarrhoeal pathogens that are defined by a HEp-2 adherence assay performed in specialist laboratories. Multilocus sequence typing (MLST) has revealed that aggregative adherence is convergent, providing an explanation for why not all EAEC hybridize with the plasmid-derived probe for this category, designated CVD432. Some EAEC lineages are globally disseminated or more closely associated with disease. Results To identify genetic loci conserved within significant EAEC lineages, but absent from non-EAEC, IS3-based PCR profiles were generated for 22 well-characterised EAEC strains. Six bands that were conserved among, or missing from, specific EAEC lineages were cloned and sequenced. One band corresponded to the aggR gene, a plasmid-encoded regulator that has been used as a diagnostic target but predominantly detects EAEC bearing the plasmid already marked by CVD432. The sequence from a second band was homologous to an open-reading frame within the cryptic enterohaemorrhagic E. coli (EHEC) O157 genomic island, designated O-island 62. Screening of an additional 46 EAEC strains revealed that the EHEC O-island 62 was only present in those EAEC strains belonging to the ECOR phylogenetic group D, largely comprised of sequence type (ST) complexes 31, 38 and 394. Conclusions The EAEC 042 gene orf1600, which lies within the EAEC equivalent of O-island 62 island, can be used as a marker for EAEC strains belonging to the ECOR phylogenetic group D. The discovery of EHEC O-island 62 in EAEC validates the genetic profiling approach for identifying conserved loci among phylogenetically related strains.